Pressure balance in the multiphase ISM of cosmologically simulated disc galaxies. Issue 3 (26th August 2020) - Gurvich, Alexander B; Faucher-Giguère, Claude-André; Richings, Alexander J; Hopkins, Philip F; Grudić, Michael Y; Hafen, Zachary; Wellons, Sarah; Stern, Jonathan; Quataert, Eliot; Chan, T K; Orr, Matthew E; Kereš, Dušan; et al.
ABSTRACT: Pressure balance plays a central role in models of the interstellar medium (ISM), but whether and how pressure balance is realized in a realistic multiphase ISM is not yet well understood. We address this question by using a set of FIRE-2 cosmological zoom-in simulations of Milky Way-mass disc galaxies, in which a multiphase ISM is self-consistently shaped by gravity, cooling, and stellar feedback. We analyse how gravity determines the vertical pressure profile as well as how the total ISM pressure is partitioned between different phases and components (thermal, dispersion/turbulence, and bulk flows). We show that, on average and consistent with previous more idealized simulations, the total ISM pressure balances the weight of the overlying gas. Deviations from vertical pressure balance increase with increasing galactocentric radius and with decreasing averaging scale. The different phases are in rough total pressure equilibrium with one another, but with large deviations from thermal pressure equilibrium owing to kinetic support in the cold and warm phases, which dominate the total pressure near the mid-plane. Bulk flows (e.g. inflows and fountains) are important at a few disc scale heights, while thermal pressure from hot gas dominates at larger heights. Overall, the total mid-plane pressure is well-predicted by the weight of the disc gas and we show that it also scales linearly with the star formation rate surface density (ΣSFR ). These results support the notion that the Kennicutt–Schmidt relation arises because ΣSFR and the gas surface density (Σg ) are connected via the ISM mid-plane pressure.